Mapping between XML and RDF via DTD - Gulati, Harvinder (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
XML has gained massive popularity for representation of data in last decades. Both HTML and XML are used as primary data formats since the existence of World Wide Web. As the amount of data is growing, need has emerged to represent the data in such a manner that it can be recognized by machines rather than only humans. The next generation web, Semantic web aims at representing large amount of data available in www in a machine understandable format. However, XML represent the structure of data and cannot serve the purpose of machine understandability and HTML is too inexpressive to be used by machines for interpretation of data. To bridge this gap between syntax and semantics, current data needs to be converted into Semantic web compatible formats and XML DTDs can directly be converted into RDF. This paper focuses on conversion of data available in XML DTDs into RDF using classes, subclasses and properties.